Mild, Efficient, and Regioselective Synthesis of Diiodophenylboronic Acid Derivatives via Metal–Iodine Exchange of 5-Substituted 1,2,3-Triiodoarenes - Al-Zoubi, Raed M.; Ibdah, Abdellatif; Al-Jammal, Walid K.; Al-Zoubi, Mazhar S.; Almasalma, Ahmad A.; McDonald, Robert (Synthesis, 2018)
Unique 2,6-diiodophenylboronic acid and 2,3-diiodophenylboronic acid derivatives have been synthesized via regioselective metal–iodine exchange (MIE) of 5-substituted 1,2,3-triiodoarenes. The regioselectivity of the reaction per se is remarkably controlled by the nature of the C5 substituent providing the desired diiodophenylboronic acids in moderate to good yields and with high site selectivity. The diiodophenylboronic acids were then examined for in vitro antimicrobial activity against four strains of bacteria Micrococcus luteus (ATCC 9341), Bacillus cereus (ATCC 11778), Escherichia coli (ATCC 25922), and Serratia marcescens (ATCC 27117) and one fungal strain Candida albicans using well diffusion assay and dilution method. It indicated that 5-fluoro-2,3-diiodophenylboronic acid possesses the most potent antibacterial and antifungal activity with MIC of 2.6 mg/mL for M. luteus and C. albicans. This report discloses a one-step protocol to access hitherto unknowns 2,6-diiodophenylboronic acid and 2,3-diiodophenylboronic acid derivatives that is scalable, good in scope, no chromatography is needed, and these compounds are difficult to prepare by other means.
Keywords: 1,2,3-triiodoarenes; 2,6-diiodophenylboronic acids; 2,3-diiodophenylboronic acids; metal–iodine exchange; antibacterial; antifungal